Cellulose-based fabric photo-thermal material as well as preparation method and application thereof
By loading polyphenol metal coordination complex and silver nanoparticles on cellulose-based fabrics, Cu-TA-Fe-Ag composite photothermal material was prepared, which solved the shortcomings of traditional photothermal materials in both high-efficiency photothermal conversion and antibacterial performance, and achieved efficient, stable and low-cost concentrated saline treatment effect.
Patent Information
- Application Number
- CN202510068080.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The prior art has high energy consumption problems when dealing with concentrated salt water, which limits its development and application. In addition, traditional photothermal materials have insufficient performance when taking into account both high photothermal conversion and antibacterial properties.
Cellulose-based fabrics are used as photothermal material, and Cu-TA-Fe-Ag composite photothermal material is formed by loading polyphenol metal coordination complexes and silver nanoparticles in the surface and pores of the cellulose fiber fabric. The material is prepared by simple immersion and coordination reduction methods, with the advantages of low cost and easy to prepare on a large scale.
An efficient solar-water vapor conversion was achieved, with the solar-water vapor conversion efficiency reaching 95.2%, and it remained stable during the 20-day cycle experiment. The material surface was free of salt-scaling and had good antibacterial properties.
Smart Images

Figure CN119754026A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wastewater treatment, and in particular relates to a cellulose-based fabric photothermal material and a preparation method and application thereof. Background Art
[0002] With the rapid development of industry, the large amount of concentrated brine produced has brought challenges to water treatment. High-concentration brine increases the difficulty and cost of water treatment, and has a negative impact on the environment and ecosystem. In addition, concentrated brine may contain valuable resources, which will lead to waste of resources if they cannot be effectively recycled. In order to meet these challenges, low-cost concentration and reduction treatment methods have become very urgent. At present, membrane separation, thermal evaporation, ion exchange and other technologies are widely used to treat concentrated brine, but these technologies have the characteristics of high energy consumption, which limits their development and application, and brings huge processing costs to enterprises. Photothermal interface evaporation technology uses solar energy to drive evaporation, has the advantages of low energy consumption, green and low carbon, and has become a promising technology for the concentration and reduction of concentrated brine.
[0003] There are three types of solar evaporation systems: bottom heating evaporation system, bulk heating evaporation system and interface heating evaporation system. The bottom heating evaporation system has a large loss of solar energy, and the solar energy utilization rate of the entire solar-driven evaporation system is only 30-45%. The bulk heating evaporation system reduces the loss of solar energy to a certain extent, but the heating process of the surrounding water by nanoparticles will inevitably transfer heat to the non-evaporation area, resulting in heat loss, and the disadvantages of carbon-based nanoparticles and metal-based nanoparticles are difficult to recycle, high cost, and easy to cause secondary pollution to the water body, which makes the bulk heating method difficult to apply on a large scale. The interface evaporation system greatly reduces the loss of solar energy, greatly increases the temperature of interface evaporation, and can effectively reduce the loss of heat to the water body, so that the interface water evaporates quickly, thereby significantly improving the utilization rate of solar energy. Therefore, solar interface evaporation concentration is currently one of the most promising ways to concentrate saline water and desalinate seawater.
[0004] In the design of efficient interfacial solar steam generators, the selection of photothermal materials is key, and the selection of substrates that load the photothermal materials is particularly important. Traditional synthetic polymers, metal substrates and semiconductors have high solar-thermal energy conversion efficiency, but their high cost also limits their large-scale application.
[0005] Cellulose is widely used as a photothermal carrier due to its good hydrophilicity, high mechanical strength, good flexibility and low cost. However, in the research on cellulose-based evaporators, high photothermal conversion performance and antibacterial properties cannot be taken into account at the same time, and the performance needs to be improved. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a cellulose-based fabric photothermal material and a preparation method and application thereof. The cellulose-based fabric photothermal material has good stability, excellent photothermal performance, and antibacterial properties.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a cellulose-based fabric photothermal material, comprising: cellulose fiber fabric, polyphenol metal coordination complex and silver nanoparticles loaded on the surface and pores of the cellulose fiber fabric;
[0009] The polyphenol metal complex includes a polyphenol copper complex, a polyphenol trivalent iron complex and a polyphenol silver complex.
[0010] Preferably, the mass percentage of the polyphenol copper complex in the cellulose-based fabric photothermal material is 1-5%, the mass percentage of the polyphenol trivalent iron complex is 1-5%, the mass percentage of the polyphenol silver complex is 1-5%, and the mass percentage of the silver nanoparticles is 2-5%.
[0011] Preferably, the cellulose fiber fabric comprises one or more of cotton cellulose fiber fabric, hemp cellulose fiber fabric and wood cellulose fiber fabric.
[0012] The present invention also provides a method for preparing the cellulose-based fabric photothermal material according to the above technical solution, comprising the following steps:
[0013] The cellulose fiber fabric is sequentially immersed in an alkaline copper salt solution, a polyphenol solution, a soluble iron salt solution and a soluble silver salt solution, and then sequentially washed and dried to obtain a cellulose-based fabric photothermal material.
[0014] Preferably, the alkaline copper salt solution is a mixed solution of copper salt and sodium hydroxide; the molar ratio of the copper salt to sodium hydroxide is 1:1-400.
[0015] Preferably, the copper salt includes one or more of copper chloride, copper nitrate and copper sulfate.
[0016] Preferably, the polyphenols in the polyphenol solution include one or more of tannic acid, phenolic ketone polyphenols and phenylpropanoid polyphenols; and the concentration of the polyphenols in the polyphenol solution is 2-4 g / L.
[0017] Preferably, the soluble iron salt in the soluble iron salt solution includes one or more of ferric chloride, ferric sulfate and ferric nitrate; and the concentration of the soluble iron salt in the soluble iron salt solution is 0.5 to 3 g / L.
[0018] The present invention also provides the use of the cellulose-based fabric photothermal material described in the above technical solution or the cellulose-based fabric photothermal material prepared by the preparation method described in the above technical solution in treating saline wastewater.
[0019] The present invention also provides a saline wastewater thermal management enhanced interface concentration system, comprising a heat collecting shed, a heat chimney and an evaporation interface; the evaporation interface is used to cover the surface of the saline wastewater; the heat collecting shed is used to cover the saline wastewater; a heat chimney is arranged on the heat collecting shed;
[0020] The evaporation interface is the cellulose-based fabric photothermal material described in the above technical solution or the cellulose-based fabric photothermal material prepared by the preparation method described in the above technical solution.
[0021] The present invention provides a cellulose-based fabric photothermal material, comprising: cellulose fiber fabric, polyphenol metal coordination complex and silver nanoparticles loaded on the surface and pores of the cellulose fiber fabric; the polyphenol metal complex comprises a polyphenol copper complex, a polyphenol trivalent iron complex and a polyphenol silver complex. The cellulose-based fabric photothermal material provided by the present invention has strong light absorption performance in the visible light range, and the solar energy-water vapor conversion efficiency can reach 95.2%, and can effectively convert light energy into heat energy, and has excellent photothermal conversion performance; and after a 20-day cycle experiment, the evaporation rate fluctuates little, and no obvious salt scaling phenomenon occurs on the surface of the material, and the water evaporation rate remains stable and can be reused; and after an antibacterial zone experiment is performed on the material, an antibacterial zone is observed around the material, indicating that the material has certain antibacterial properties.
[0022] The present invention also provides a method for preparing the above-mentioned cellulose-based fabric photothermal material. A photothermal composite material is generated on a cellulose-based fabric by a simple soaking and coordination reduction method. The preparation process is simple, the preparation cost is low, and it is easy to prepare on a large scale.
[0023] The present invention also provides the application of the above-mentioned cellulose-based fabric photothermal material in a thermal management enhanced interface concentration system for saline wastewater, and further improves the evaporation rate by constructing a hot chimney evaporation system. Sunlight irradiates the solar shed, and the evaporation interface under the solar shed absorbs the solar radiation energy that passes through the covering layer, and heats the air between the water surface and the covering layer of the solar shed, so that the air temperature in the solar shed increases, the density decreases, and rises along the chimney. The dry air around the solar shed enters the system, thereby forming a high-temperature air circulation flow, increasing the water vapor partial pressure difference between the water interface and the high-temperature dry air, thereby further enhancing the evaporation of salt water. The present invention reduces the heat loss of the evaporation interface through the hot chimney structure and evaporation system, and utilizes the thermal pressure generated by the hot chimney to circulate the air continuously, thereby achieving an enhanced interface evaporation effect. Tests have shown that the cellulose-based fabric photothermal material prepared by the present invention has good wettability and air permeability during the evaporation process. Under one sun, the water evaporation rate of the cellulose-based fabric photothermal material can reach 1.43kgm -2 h -1 In the hot chimney system, the water evaporation rate can reach 2.52kgm -2 h -1 , the solar-water vapor conversion efficiency is as high as 95.2%. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the structure of the enhanced interfacial concentration system for thermal management of saline wastewater;
[0025] Figure 2 This is a scanning electron microscope image of the pure cotton cloth used in Example 1;
[0026] Figure 3 This is a scanning electron microscope image of the Cu-TA-Fe-Ag composite photothermal material prepared in Example 1;
[0027] Figure 4 This is a scanning electron microscope image of the Cu-TA-Fe composite photothermal material prepared in Comparative Example 1;
[0028] Figure 5 This is a scanning electron microscope image of the Cu-TA composite photothermal material prepared in Comparative Example 2;
[0029] Figure 6 This is a scanning electron microscope image of the Cu composite photothermal material prepared in Comparative Example 3;
[0030] Figure 7 This is a graph showing the stability test results of the Cu-TA-Fe-Ag composite photothermal material prepared in Example 1;
[0031] Figure 8 This is the Vis-NIR absorption spectrum of the Cu-TA-Fe-Ag composite photothermal material prepared in Example 1. DETAILED DESCRIPTION
[0032] The present invention provides a cellulose-based fabric photothermal material, comprising: cellulose fiber fabric, polyphenol metal coordination complex and silver nanoparticles loaded on the surface and pores of the cellulose fiber fabric;
[0033] The polyphenol metal complex includes a polyphenol copper complex, a polyphenol trivalent iron complex and a polyphenol silver complex.
[0034] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0035] The cellulose-based fabric photothermal material provided by the present invention includes: cellulose fiber fabric. In the present invention, the cellulose fiber fabric preferably includes one or more of cotton cellulose fiber fabric, hemp cellulose fiber fabric, and wood cellulose fiber fabric, and is more preferably cotton cellulose fiber fabric; the cotton cellulose fiber fabric is preferably cotton cloth; the thickness of the cellulose fiber fabric is preferably 1 to 5 cm, and more preferably 2 to 3 cm.
[0036] The cellulose-based fabric photothermal material provided by the present invention comprises: a polyphenol metal coordination complex and silver nanoparticles loaded on the surface and pores of the cellulose fiber fabric; the polyphenol metal complex comprises a polyphenol copper complex, a polyphenol trivalent iron complex and a polyphenol silver complex.
[0037] In the present invention, the mass percentage of the polyphenol copper complex in the cellulose-based fabric photothermal material is preferably 1-5%, more preferably 2-3%, the mass percentage of the polyphenol trivalent iron complex is preferably 1-5%, more preferably 2-4%, the mass percentage of the polyphenol silver complex is preferably 1-5%, more preferably 2-3%, and the mass percentage of the silver nanoparticles is preferably 2-5%, more preferably 3-4%.
[0038] The cellulose-based fabric photothermal material provided by the present invention has good stability, excellent photothermal performance, and antibacterial properties.
[0039] The present invention also provides a method for preparing the cellulose-based fabric photothermal material according to the above technical solution, comprising the following steps:
[0040] The cellulose fiber fabric is sequentially immersed in an alkaline copper salt solution, a polyphenol solution, a soluble iron salt solution and a soluble silver salt solution, and then sequentially washed and dried to obtain a cellulose-based fabric photothermal material.
[0041] The invention soaks the cellulose fiber fabric in alkaline copper salt solution, polyphenol solution, soluble iron salt solution and soluble silver salt solution in sequence.
[0042] In the present invention, the alkaline copper salt solution is preferably a mixed solution of copper salt and sodium hydroxide; the copper salt preferably includes one or more of copper chloride, copper nitrate and copper sulfate, and is more preferably copper chloride; the sodium hydroxide preferably includes sodium hydroxide and / or potassium hydroxide, and is more preferably sodium hydroxide; the molar ratio of the copper salt to sodium hydroxide is preferably 1:1-400, and is more preferably 1:200-350; the immersion time in the alkaline copper salt solution is preferably 12-24h, and is more preferably 15-20h.
[0043] In the present invention, the method for preparing the copper salt solution is preferably to mix copper salt and water and perform ultrasonic treatment to obtain a copper salt solution; the ultrasonic treatment is performed at room temperature; the power of the ultrasonic treatment is preferably 10 to 450 W, more preferably 100 to 300 W; the time of the ultrasonic treatment is preferably 5 to 20 min, more preferably 10 to 15 min; the concentration of the copper salt in the copper salt solution is preferably 1 to 3 g / L, more preferably 1 g / L.
[0044] In the present invention, the method for preparing the sodium hydroxide solution is preferably to mix sodium hydroxide and water and perform ultrasonic treatment to obtain the sodium hydroxide solution; the ultrasonic treatment is performed at room temperature; the power of the ultrasonic treatment is preferably 10 to 450 W, more preferably 100 to 300 W; the time of the ultrasonic treatment is preferably 5 to 20 min, more preferably 10 to 15 min; the mass concentration of sodium hydroxide in the sodium hydroxide solution is preferably 5 to 20%, more preferably 10 to 15%.
[0045] In the present invention, the method for preparing the mixed solution of copper salt and sodium hydroxide is preferably to mix the copper salt solution and the sodium hydroxide solution, and perform ultrasonic treatment at room temperature to obtain the mixed solution of copper salt and sodium hydroxide; the power of the ultrasonic treatment is preferably 10 to 450 W, more preferably 100 to 300 W; the time of the ultrasonic treatment is preferably 5 to 20 min, more preferably 10 to 15 min.
[0046] Before impregnation, the present invention preferably soaks the cellulose fiber fabric in ethanol to remove impurities, and then washes and dries in sequence; the soaking time is preferably 10 to 60 minutes, more preferably 20 to 30 minutes; the washing is preferably carried out with deionized water; the drying is preferably carried out at room temperature; the drying time is preferably 5 minutes to 3 hours, more preferably 10 minutes to 3 hours.
[0047] After the immersion in the alkaline copper salt solution is completed, the present invention preferably washes the cellulose fiber fabric after the immersion with water until it becomes neutral; the washing is preferably carried out with deionized water.
[0048] The present invention immerses the cellulose fiber fabric in an alkaline copper salt solution, firstly destroys the hydrogen bond network connecting the cellulose chains in an alkaline environment, and then diffuses the Cu ions into the expanded cellulose material to coordinate with the hydroxyl groups on the cellulose chains to form a stable copper ion-cellulose complex.
[0049] In the present invention, the method for preparing the polyphenol solution is preferably to mix polyphenol and water and perform ultrasonic treatment to obtain the polyphenol solution; the ultrasonic treatment is performed at room temperature; the power of the ultrasonic treatment is preferably 10 to 450 W, more preferably 100 to 300 W; the time of the ultrasonic treatment is preferably 5 to 20 min, more preferably 10 to 15 min.
[0050] In the present invention, the polyphenol in the polyphenol solution preferably includes one or more of tannic acid, phenolic phenols and phenylpropane polyphenols, more preferably tannic acid; the concentration of the polyphenol in the polyphenol solution is preferably 2-4 g / L, more preferably 1-3 g / L; the immersion time in the polyphenol solution is preferably 1-4 h, more preferably 2 h.
[0051] After the immersion in the polyphenol solution is completed, the present invention preferably washes the cellulose fiber fabric after the immersion; the washing is preferably carried out with deionized water.
[0052] The present invention immerses the cellulose fiber fabric loaded with copper ions in a polyphenol solution. The natural polyphenol substance containing catechol structure can provide lone pair electrons and form a chelate with Cu(II) ions, so the polyphenol and the copper ions form a complex through coordination.
[0053] In the present invention, the soluble iron salt in the soluble iron salt solution preferably includes one or more of ferric chloride, ferric sulfate and ferric nitrate, and is more preferably ferric chloride; the concentration of the soluble iron salt in the soluble iron salt solution is preferably 0.5 to 3 g / L, and is more preferably 1 to 2 g / L; the immersion time in the soluble iron salt solution is preferably 1 to 4 hours, and is more preferably 2 to 3 hours.
[0054] In the present invention, the method for preparing the soluble iron salt solution is preferably to mix the soluble iron salt and water and perform ultrasonic treatment to obtain the soluble iron salt solution; the ultrasonic treatment is performed at room temperature; the power of the ultrasonic treatment is preferably 10 to 450 W, more preferably 100 to 300 W; the time of the ultrasonic treatment is preferably 5 to 20 min, more preferably 10 to 15 min.
[0055] After the immersion in the soluble iron salt solution is completed, the present invention preferably washes the cellulose fiber fabric after the immersion; the washing is preferably carried out with deionized water.
[0056] The present invention immerses the cellulose fiber fabric loaded with the polyphenol-copper ion complex in a soluble iron salt solution. The benzene ring in the polyphenol structure has two adjacent phenolic hydroxyl groups, which can react with the iron ions in the form of oxygen anions to form a five-membered ring complex with stable chemical properties. Therefore, the polyphenol and the trivalent iron ion form a complex through coordination.
[0057] In the present invention, the soluble silver salt in the soluble silver salt solution preferably includes one or more of silver nitrate, silver chloride and silver ammonia; the concentration of the soluble silver salt in the soluble silver salt solution is preferably 0.5 to 4 g / L, more preferably 1 to 3 g / L; the immersion time in the soluble silver salt solution is preferably 6 to 24 hours, more preferably 10 to 20 hours.
[0058] In the present invention, the method for preparing the soluble silver salt solution is preferably to mix the soluble silver salt and water and perform ultrasonic treatment to obtain the soluble silver salt solution; the ultrasonic treatment is performed at room temperature; the power of the ultrasonic treatment is preferably 10 to 450 W, more preferably 100 to 300 W; the time of the ultrasonic treatment is preferably 5 to 20 min, more preferably 10 to 15 min.
[0059] The present invention immerses a cellulose fiber fabric loaded with a polyphenol-copper ion-ferric ion complex in a soluble silver salt solution. When there are at least two adjacent phenolic hydroxyl groups on the benzene ring in the polyphenol structure, the phenolic hydroxyl groups can chelate with the silver ions, so that part of the silver ions and the polyphenol form a complex through coordination, and part of the anions are reduced by the phenolic hydroxyl groups in the polyphenol to form silver nanoparticles.
[0060] After the immersion in the soluble silver salt solution is completed, the present invention sequentially washes and dries the impregnated cellulose fiber fabric to obtain a cellulose-based fabric photothermal material. In the present invention, the washing is preferably carried out with deionized water; the drying time is preferably 5 minutes to 3 hours, more preferably 10 minutes to 3 hours; the drying temperature is preferably room temperature.
[0061] The present invention generates a photothermal composite material on a cellulose-based cloth by a simple soaking and coordination reduction method, and has a simple preparation process, low preparation cost, and is easy to prepare on a large scale.
[0062] The present invention also provides the use of the cellulose-based fabric photothermal material described in the above technical solution or the cellulose-based fabric photothermal material prepared by the preparation method described in the above technical solution in treating saline wastewater.
[0063] The present invention also provides a salt-containing wastewater thermal management enhanced interface concentration system, comprising a heat collection shed, a thermal chimney and an evaporation interface; the evaporation interface is used to cover the surface of the salt-containing wastewater; the heat collection shed is used to cover the salt-containing wastewater; a thermal chimney is arranged on the heat collection shed; the evaporation interface is the cellulose-based fabric photothermal material described in the above technical scheme or the cellulose-based fabric photothermal material prepared by the preparation method described in the above technical scheme.
[0064] In the present invention, the distance between the heat collecting shed and the evaporation interface is preferably 3 to 10 cm, more preferably 5 to 8 cm.
[0065] Figure 1 The schematic diagram of the structure of the thermal management enhanced interface concentration system for saline wastewater is shown in Figure 2. Figure 1 As shown, the thermal management enhanced interface concentration system for saline wastewater includes a heat collection shed, a thermal chimney and an evaporation interface (cellulose-based fabric photothermal material); the evaporation interface is used to cover the surface of the saline wastewater; the heat collection shed is used to cover the saline wastewater; and a thermal chimney is arranged on the heat collection shed.
[0066] The present invention further improves the evaporation rate by constructing a thermal chimney evaporation system. Sunlight irradiates the solar shed, and the evaporation interface under the solar shed absorbs the solar radiation energy that passes through the covering layer, and heats the air between the water surface and the covering layer of the solar shed, so that the air temperature in the solar shed increases, the density decreases, and rises along the chimney. The dry air around the solar shed enters the system, thereby forming a high-temperature air circulation flow, increasing the water vapor partial pressure difference between the water interface and the high-temperature dry air, thereby further enhancing the evaporation of salt water. The present invention reduces the heat loss of the evaporation interface through the thermal chimney structure and evaporation system, and utilizes the thermal pressure generated by the thermal chimney to continuously circulate the air to achieve an enhanced interface evaporation effect. Tests have shown that the cellulose-based fabric photothermal material prepared by the present invention has good wettability and air permeability during the evaporation process. Under one sunlight, the water evaporation rate of the cellulose-based fabric photothermal material can reach 1.43kgm -2 h -1 In the hot chimney system, the water evaporation rate can reach 2.52kgm - 2 h -1 , the solar-water vapor conversion efficiency is as high as 95.2%.
[0067] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0068] Example 1
[0069] 1) Prepare solution
[0070] Take 10g of sodium hydroxide and dissolve it in 90mL of deionized water. Ultrasonicate at 300W power for 10min at room temperature. After the ultrasonication, a 10wt% sodium hydroxide solution is prepared.
[0071] 0.1 g of copper chloride was dissolved in 100 mL of deionized water, and ultrasonicated at 300 W power for 10 min at room temperature. After the ultrasonication, a copper chloride solution with a copper chloride concentration of 1 g / L was obtained. The sodium hydroxide solution and the copper chloride solution were mixed evenly, and ultrasonicated at 300 W power for 10 min at room temperature to prepare a mixed solution of sodium hydroxide and copper chloride, i.e., an alkaline copper salt solution;
[0072] Take 0.2 g of tannic acid (TA) and dissolve it in 100 mL of deionized water. Ultrasonicate at 300 W power for 10 min at room temperature to prepare a 2 g / L TA solution for use.
[0073] Take 0.1g of anhydrous ferric chloride and dissolve it in 100mL of deionized water, and ultrasonicate it at 300W power for 10min at room temperature to prepare a ferric chloride solution with a concentration of 1g / L for use;
[0074] Take 0.1g of silver chloride and dissolve it in 100mL of deionized water, and ultrasonicate it at 300W power for 10min at room temperature to prepare a silver chloride solution with a silver chloride concentration of 1g / L for use;
[0075] 2) Preparation of cellulose-based fabric photothermal materials
[0076] The cotton cloth was soaked in ethanol for 30 minutes to remove impurities, washed with deionized water, and dried at room temperature for 3 hours before use;
[0077] The cleaned cotton cloth was soaked in an alkaline copper salt solution for 24 hours, washed with deionized water until neutral, and then immersed in a TA solution for 2 hours. The cotton cloth was then washed with deionized water and immersed in a ferric chloride solution for 1 hour. The cotton cloth was taken out, washed with deionized water, and immersed in a silver chloride solution for 12 hours. Finally, it was repeatedly washed with deionized water and dried at room temperature for 3 hours to obtain a cellulose-based fabric photothermal material, namely, a Cu-TA-Fe-Ag composite photothermal material.
[0078] Comparative Example 1
[0079] The preparation process is the same as that of Example 1, except that the immersion in the silver chloride solution is reduced to obtain the Cu-TA-Fe composite photothermal material.
[0080] Comparative Example 2
[0081] The preparation process is the same as that of Example 1, except that the immersion in the ferric chloride solution and the silver chloride solution is reduced to obtain the Cu-TA composite photothermal material.
[0082] Comparative Example 3
[0083] The preparation process is the same as that of Example 1, except that the immersion in TA solution, ferric chloride and silver chloride solution is reduced to obtain the Cu composite photothermal material.
[0084] Application Example 1
[0085] A thermal management enhanced interface concentration system for saline wastewater comprises a heat collecting shed, a thermal chimney and an evaporation interface; the evaporation interface covers the surface of the saline wastewater; the heat collecting shed covers the saline wastewater; a thermal chimney is arranged in the center of the heat collecting shed; the evaporation interface is the cellulose-based fabric photothermal material prepared in Example 1, and the distance between the heat collecting shed and the evaporation interface is 5 cm.
[0086] Application Example 2
[0087] The difference from Application Example 1 is that the distance between the heat collecting shed and the evaporation interface is 10 cm.
[0088] Comparative application example 1
[0089] The difference from Application Example 1 is that the evaporation interface is the Cu-TA-Fe composite photothermal material prepared in Comparative Example 1.
[0090] Comparative Application Example 2
[0091] The difference from Application Example 1 is that the evaporation interface is the Cu-TA composite photothermal material prepared in Comparative Example 2.
[0092] Comparative Application Example 3
[0093] The difference from Application Example 1 is that the evaporation interface is the Cu composite photothermal material prepared in Comparative Example 3.
[0094] Performance Testing
[0095] (1) The water evaporation rate of the composite photothermal materials prepared in Example 1 and Comparative Examples 1 to 3 was tested. The experimental climate conditions included: humidity 35%, air temperature 20°C, water temperature 20°C, wind speed 2m / s, and solar radiation intensity 1kW / m. The results are shown in Table 1.
[0096] Table 1 Water evaporation rate of composite photothermal materials prepared in Example 1 and Comparative Examples 1 to 3
[0097]
[0098] It can be seen from Table 1 that the water evaporation rate of the Cu-TA-Fe-Ag composite photothermal material prepared in Example 1 is higher than that of the Cu-TA-Fe composite photothermal material prepared in Comparative Example 1, and higher than that of the Cu-TA composite photothermal material prepared in Comparative Example 2, that is, the water evaporation rate of the Cu-TA-Fe-Ag composite photothermal material is optimal.
[0099] (2) The water evaporation rate and solar energy-water vapor conversion efficiency of the thermal management enhanced interface concentration system for salt-containing wastewater prepared in Examples 1-2 and Comparative Application Examples 1-3 were tested. The experimental climatic conditions included: humidity 35%, air temperature 20°C, water temperature 20°C, wind speed 2m / s, and solar radiation intensity 1kW / m. The results are shown in Table 2.
[0100] Table 2 Water evaporation rate and solar energy-water vapor conversion efficiency in the thermal management enhanced interface concentration system of salt-containing wastewater prepared in Application Examples 1-2 and Comparative Application Examples 1-3
[0101]
[0102] It can be seen from Table 2 that the water evaporation rate and solar energy-water vapor conversion efficiency of Application Example 1 are the highest, and it is the optimal solution, that is, the selected material is the prepared Cu-TA-Fe-Ag composite photothermal material and the distance between the collector shed and the evaporation interface is 5 cm.
[0103] (3) Scanning electron microscope tests were performed on the pure cotton cloth used in Example 1, the prepared Cu-TA-Fe-Ag composite photothermal material, the Cu-TA-Fe composite photothermal material prepared in Comparative Example 1, the Cu-TA composite photothermal material prepared in Comparative Example 2, and the Cu composite photothermal material prepared in Comparative Example 3. The results are as follows: Figures 2 to 6 shown.
[0104] Depend on Figures 2 to 6 It can be seen that compared with pure cotton cloth and the Cu composite photothermal material prepared in Comparative Example 3, the Cu-TA composite photothermal material prepared in Comparative Example 2, the Cu-TA-Fe composite photothermal material prepared in Comparative Example 1, and the Cu-TA-Fe-Ag composite photothermal material prepared in Example 1 all have particles, and the particles of the prepared Cu-TA-Fe-Ag composite photothermal material are the most dense. The metal particle loading is beneficial to the photothermal conversion efficiency and improves its evaporation efficiency.
[0105] (4) The stability test of the Cu-TA-Fe-Ag composite photothermal material prepared in Example 1 was carried out. The results are as follows: Figure 7As shown in the figure, it can be seen that the water evaporation rate of the Cu-TA-Fe-Ag composite photothermal material prepared by the present invention does not fluctuate much after a 20-day cycle experiment and remains stable, and there is no obvious salt scaling phenomenon on the surface of the material, indicating that the Cu-TA-Fe-Ag composite photothermal material prepared by the present invention is stable and can be reused.
[0106] (5) Figure 8 This is a Vis-NIR absorption spectrum of the Cu-TA-Fe-Ag composite photothermal material prepared in Example 1. As can be seen from the figure, the Cu-TA-Fe-Ag composite photothermal material prepared by the present invention has strong light absorption performance in the visible light range, and the solar energy conversion efficiency can reach 95.2%.
[0107] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A cellulose-based fabric photothermal material, characterized in that: include: Cellulose fiber fabric, polyphenol metal coordination complex and silver nanoparticles loaded on the surface and pores of the cellulose fiber fabric; The polyphenol metal complex includes a polyphenol copper complex, a polyphenol trivalent iron complex and a polyphenol silver complex.
2. The cellulose-based fabric photothermal material according to claim 1, characterized in that: The mass percentage of the polyphenol copper complex in the cellulose-based fabric photothermal material is 1-5%, the mass percentage of the polyphenol trivalent iron complex is 1-5%, the mass percentage of the polyphenol silver complex is 1-5%, and the mass percentage of the silver nanoparticles is 2-5%.
3. The cellulose-based fabric photothermal material according to claim 1, characterized in that: The cellulose fiber fabric includes one or more of cotton cellulose fiber fabric, hemp cellulose fiber fabric and wood cellulose fiber fabric.
4. The method for preparing the cellulose-based fabric photothermal material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The cellulose fiber fabric is sequentially immersed in an alkaline copper salt solution, a polyphenol solution, a soluble iron salt solution and a soluble silver salt solution, and then sequentially washed and dried to obtain a cellulose-based fabric photothermal material.
5. The preparation method according to claim 4, characterized in that The alkaline copper salt solution is a mixed solution of copper salt and sodium hydroxide; the molar ratio of the copper salt to sodium hydroxide is 1:1-400.
6. The preparation method according to claim 5, characterized in that The copper salt includes one or more of copper chloride, copper nitrate and copper sulfate.
7. The preparation method according to claim 4, characterized in that The polyphenols in the polyphenol solution include one or more of tannic acid, phenolic ketone polyphenols and phenylpropane polyphenols; the concentration of the polyphenols in the polyphenol solution is 2-4 g / L.
8. The preparation method according to claim 4, characterized in that The soluble iron salt in the soluble iron salt solution includes one or more of ferric chloride, ferric sulfate and ferric nitrate; the concentration of the soluble iron salt in the soluble iron salt solution is 0.5-3 g / L.
9. Use of the cellulose-based fabric photothermal material according to any one of claims 1 to 3 or the cellulose-based fabric photothermal material prepared by the preparation method according to any one of claims 4 to 8 in treating saline wastewater.
10. A thermal management enhanced interface concentration system for saline wastewater, characterized in that: It includes a heat collecting shed, a heat chimney and an evaporation interface; the evaporation interface is used to cover the surface of the saline wastewater; the heat collecting shed is used to cover the saline wastewater; a heat chimney is arranged on the heat collecting shed; The evaporation interface is the cellulose-based fabric photothermal material according to any one of claims 1 to 3 or the cellulose-based fabric photothermal material prepared by the preparation method according to any one of claims 4 to 8.
Citation Information
Patent Citations
Preparation method of polyphenol modified nano-silver carrying antibacterial fabric
CN105839419A
Dual passive solar water treatment system
CN112978830A
PH response type controlled-release sterilization coating as well as preparation method and application thereof
CN115814154A
Preparation method of moisture-controllable high-salt-tolerance hydrogel interface evaporation fabric
CN117265874A